2014
DOI: 10.1080/09647775.2014.919175
|View full text |Cite
|
Sign up to set email alerts
|

Art museum visitors: interaction strategies for sharing experiences

Abstract: Prior research into the museum experience has prioritised the study of the visit itself, opposing the individual experience of visitors who attend alone to the social experience of those who attend accompanied. In this research, however, we study the social dimension of the art museum experience holistically, that is, before, during, and after the visit. We gathered data from 21 in-depth interviews, transcribed verbatim and analysed with the aid of computer-assisted qualitative data analysis software tools. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, existing approaches to museum displays of information often do not seem to cater to groups, while very few studies explicitly attend to how people engage with museum exhibits in groups (Davies & Heath, 2013;Tolmie, 2014). Even in those contexts where sociality has been accounted for, it can often seem narrowly conceived, ignoring pre-and post-visit experience as well as the complexities of the visit itself, which may entail both shared and independent encounters (e.g., L-pez Sintas et al, 2014). Indeed visitors themselves may still hold expectations that prompt them to quietly absorb information individually, rather than challenge and engage with it as a group (Chang, 2006;Katifori et al, 2016).…”
Section: The Museum As a Social Spacementioning
confidence: 99%
“…However, existing approaches to museum displays of information often do not seem to cater to groups, while very few studies explicitly attend to how people engage with museum exhibits in groups (Davies & Heath, 2013;Tolmie, 2014). Even in those contexts where sociality has been accounted for, it can often seem narrowly conceived, ignoring pre-and post-visit experience as well as the complexities of the visit itself, which may entail both shared and independent encounters (e.g., L-pez Sintas et al, 2014). Indeed visitors themselves may still hold expectations that prompt them to quietly absorb information individually, rather than challenge and engage with it as a group (Chang, 2006;Katifori et al, 2016).…”
Section: The Museum As a Social Spacementioning
confidence: 99%
“…Both positions were talked about as stressful and unfulfilling by all participants. As other studies have indicated, not anyone can serve as an appropriate museum companion, visitors need a shared language in which the experience can be discussed (Sintas et al, 2014) and in addition, keep a similar pace.…”
Section: Feel Like Dancing and Problems Of Keeping The Same Pacementioning
confidence: 99%
“…When studying interactions between personal and social contexts, researchers usually focus on visitor companionship, and social information is mainly based on their communication with accompanying visitors [ 27 ]. Although some have tried to use personal information as social information, such as by using SNS in a museum learning context [ 28 ] and social tagging systems that gather visitors’ thoughts [ 29 ], few studies have examined the application of social information data to enhance the visitor experience.…”
Section: Introductionmentioning
confidence: 99%